Mengaplikasikan Model Kathryn E. Barnard dalam Memberikan Asuhan Keperawatan pada Anak Sudden Infant Death Syndrome dengan Gangguan Pertukaran Gas - Mayangsari, Denny Novita (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Deaths in healthy infants less than one year old with no known cause are called sudden infant death syndrome (SIDS). There are several risk factors for SIDS: sleeping on the stomach has the highest risk for SIDS between 1.7 and 12.9 times the risk of sleeping on the back. Lying on the side also increases the risk. This position is unstable and babies can easily roll onto their stomachs. Sleeping on your back has the lowest risk for SIDS and is recommended. Infants exposed to cigarette smoke may be at risk for SIDS. Sudden death with other causes is the role of parents. This principle is closely related to Kathryn E. Barnard's nursing model theory, which focuses on parent-infant interactions and the environment. This theory focuses on development to measure reactions to feeding, environment and health education.